PEMODELAN MATEMATIKA PADA PENGELOLAAN PERIKANAN TERBARUKAN - Susilawati, Nani (UNIVERSITAS NEGERI PADANG, 2025)
Fisheries are natural resources that can be renewed (renewable) but are limited. The current state of fisheries is threatened with extinction due to overexploitation. Therefore, a mathematical model was created. The purpose of this study was to determine the form of a mathematical model in renewable fisheries management and to interpret the results of the analysis of the model. This research is a basic or theoretical research. This model is in the form of a non-linear system of differential equations. This model studies the dynamics between two components, namely tiger prawns (prey) and populations consuming prey species as alternative food (predators) with two areas, namely protected areas and unprotected areas. This model uses the Holling II response function and the logistic growth model. From the analysis of the model, there are three equilibrium points, which are local asymptotically stable.